The Effectiveness of Academic Information System Utilization and Digital Literacy as the Efforts to Improve Students’ Service Quality - Iswan, Iswan; Bahar, Herwina; Ismah, Ismah; Lestari, Suci Mulya (Journal of Education and Training, 2022)
The aim of this research is to measure the effectiveness of Academic Information Sytem and Digital Literacy utilized to serve the students of Faculty Education Muhammadiyah University of Jakarta. This research applied quantitative descriptive method which involved 90 students as respondents selected randomly. In collecting the data, a-5 Likert-scale questionnaire measuring the influence of digital literacy, the effectiveness of academic information system and students’ attitudes toward service quality and satisfaction was used as the instrument in collecting the data. The data then being analyzed through t-test and path analysis. The results of the study proved that those two variables were correlated positively and significantly in which the statistical analysis of t-test resulted tcal>Ttable=2.77>1.98 and Pvalue<0.05=0.006<0.05), while in the effort of improving service quality to the students, very high significant results were also obtained, proven by statistical test of (69.969>1.98 and 0.000<0.05). These findings were also strengthened by the statistical test of Academic Information System effectiveness and digital literacy which achieved the scores of 2.803>1.98, and 0.005<0.05.